PENGARUH KONSENTRASI KEPEMILIKAN SAHAM DAN LEVERAGE TERHADAP PENERAPAN AKUNTANSI KONSERVATIF PADA PERUSAHAAN SEKTOR KEUANGAN DI BURSA EFEK INDONESIA - OKTAVINA ZENNIAR, ANNISA; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2018)
Accounting conservatism is an accountan?s tendency to require a higher degree of verification for recognizing ?good news? than ?bad news? in financial statements. The existence of agency relationship will lead to an agency problem. Accounting conservatism is a solution to resolve agency problem. This study aims to examine the influence between share ownersihp concentration and leverage to the application of accounting conservatism of the company that listed in financial sector Indonesian Stock Exchange (IDX) year 2009-2016. The method used in this study is quantitative with the techniques of collecting documentation use the annual reports and financial statements of the company, with the company is 168 observations. This research use multiple linier regression analysis. The result of this research shows that both share ownership concentration and leverage has no effect to the application of accounting conservatism of the company that listed in financial sector Indonesian stock exchange. Keywords: Share Ownership Concentration, Leverage, Accounting Conservatism.